Relationships between running mechanics and energy cost of running at the end of a triathlon and a marathon - Hausswirth, C.; Bigard, A. X.; Guezennec, C. Y. (International Journal of Sports Medicine, 1997)
The purpose of the present study was to check the increase in energy cost of running at the end of a triathlon and a marathon and to link the decrease in energy cost of running with running kinematic parameters. Seven well-trained triathletes performed 3 experimental trials: a 2 h 15 min triathlon (30 min swimming, 60 min cycling and 45 min treadmill running), a 2 h 15 min marathon where the last 45 min (MR) were run at the same speed as the triathlon run (TR) (i.e. 75% of maximal aerobic speed), and a 45 min isolated run (IR) done at the same speed. Oxygen uptake (VO2), minute ventilation (VE), heart rate (HR), respiratory exchange ratio (RER) and kinematic data were recorded during the 3 exercise runs. The results confirm a higher energy cost during MR compared with TR (+ 3.2%; p <0.05) and IR (+ 11.7%; p <0.01). The triathlon and the marathon were associated with greater weight loss (1.6 +/- 0.02 kg; p <0.01) than the isolated run (0.7 +/- 0.2 kg). After cycling, the mean stride length in TR1 was lower during IR1 and increased at the end of TR. The results show that MR led to decrease in stride length compared with IR. After cycling, the triathletes adopted a more forward leaning posture and the trunk gradient was less marked during the marathon. Moreover, the extension of the knee at foot-strike and the maximal knee angle in non-support phase both increased during MR compared with TR and IR. However, it appears that no single kinematic variable can fully explain the decrease in running efficiency: it seems that running economy during a triathlon and a marathon are linked to global alterations of many different parameters.